Sosialisasi dan Pemberian Makanan Tambahan (PMT) Kukis Ubi Ungu sebagai Upaya Peningkatan Kreativitas Pengolahan Makanan di Desa Kemiri - Anabela Romaito Pangaribuan; Destian Fitra Andika; Nadila Anggi Praseti; Muhammad Wildan Alfirdaus; Kansa Amelia Sari; Della Amalia Seviana; Rafy Larepa Almanda; Alifia Putri Sabilla; Yohana Patrecia; Lyla Fadillah; Vania Aisya Putri; Anwar Widjaya Kusuma; Asep Purwo Yudi Utomo (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service program was conducted in Kemiri Village with the aim of enhancing mothers’ creativity in processing local food, particularly purple sweet potatoes, into more varied and attractive products. Purple sweet potatoes were chosen due to their high nutritional content, including antioxidants, dietary fiber, and natural sweetness favored by children. The implementation method included socialization on the benefits of purple sweet potatoes and the importance of variety in Supplementary Feeding (PMT), explanation of the purple sweet potato cookies recipe, and distribution of the products to participants. A total of 23 participants attended, consisting of mothers of TK Mardi Luhur students and posyandu cadres. The results showed that participants responded positively to the innovation of purple sweet potato cookies as a healthy and nutritious snack alternative. Through this activity, the mothers gained new knowledge about purple sweet potato processing as well as practical skills that can be applied at home. Furthermore, they became more aware of the nutritional benefits of purple sweet potatoes, which can be integrated into supplementary feeding for children. This activity also aimed to increase community engagement in utilizing local ingredients to enhance family nutrition. As a result, this community service activity not only introduced innovative local food products but also has the potential to support supplementary feeding programs at posyandu. The knowledge and skills gained by the participants are expected to contribute to better nutrition for children and support the sustainable use of local resources in the community, promoting health and well-being in the long term